Palliative and hegemonic dimensions of conservatism: the mitigating role of institutional trust in shaping attitudes toward migrants and migration policy preferences - Grežo, Matúš; Adamus, Magdalena; Tencerová, Jana (Frontiers in Psychology, 2024)
The study explores the links between palliative and hegemonic dimensions of conservatism, attitudes toward migrants and restrictive migration policy preferences. Participants reported on their palliative dimension (social conservatism, traditionalism) and hegemonic dimension (social dominance orientation, collective narcissism) of conservatism, trust in government, attitudes toward migrants, and restrictive migration policy preferences. The results show that both dimensions of conservatism are indirectly linked to more restrictive migration policy preferences through negative attitudes toward migrants. Moreover, the present study indicates that increasing institutional trust may be an effective mechanism mitigating negative attitudes toward migrants for individuals high in the palliative dimension of conservatism.